Moderation of inflation on the macroeconomic effect on gold futures prices - Mochammad Rizaldy Insan Baihaqqy; Emawati, Nani; Purnamasari, Laely (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2024)
Investment is a way to be able to live more safely in the future. There are investment instruments, but historically, gold is an investment instrument that is still in demand by investors even though many new investment instruments have emerged, such as crypto. This is because gold is considered a safe investment when the world economy is in a crisis. This study uses a quantitative approach that uses macroeconomic and gold futures monthly data for 2016-2020. Based on the results of the study, it shows that interest rates have a negative influence on gold futures prices, meaning that the lower the interest rate, the higher the gold futures price. Exchange rates show no effect on gold futures prices. Inflation has a negative effect on gold futures prices, meaning that the smaller the inflation, the higher the gold futures prices. Inflation as a moderating variable shows the ability to change and strengthen the effect of interest rates and inflation on gold futures prices. The results of this study indicate the importance of portfolio diversification, because gold futures prices have different characteristics from stock prices.